Effects of oral contraceptives on sympathetic nerve activity during orthostatic stress in young, healthy women - Carter, Jason R. (American Physiological Society, 2010)
Recent studies report that the menstrual cycle alters sympathetic neural responses to orthostatic stress in young, eumenorrheic women. The purpose of the present study was to determine whether oral contraceptives (OC) influence sympathetic neural activation during an orthostatic challenge. Based on evidence that sympathetic baroreflex sensitivity (BRS) is increased during the “low hormone” (LH) phase (i.e., placebo pills) in women taking OC, we hypothesized an augmented muscle sympathetic nerve activity (MSNA) response to orthostatic stress during the LH phase. MSNA, mean arterial pressure (MAP), and heart rate (HR) were recorded during progressive lower body negative pressure (LBNP; −5, −10, −15, −20, −30, −40 mmHg; 3 min/stage) in 12 healthy women taking OC (age 22 ± 1 years). Sympathetic BRS was assessed by examining relations between spontaneous fluctuations of diastolic arterial pressure and MSNA. Subjects were examined twice: once during LH phase and once ∼3 wk after LH during the “high hormone” phase (randomized order). Resting MSNA (10 ± 2 vs. 13 ± 2 bursts/min), MAP (85 ± 3 vs. 84 ± 3 mmHg), and HR (62 ± 2 vs. 65 ± 3 beats/min) were not different between phases. MSNA and HR increased during progressive LBNP (P < 0.001), and these increases were similar between phases. Progressive LBNP did not change MAP during either phase. Sympathetic BRS increased during progressive LBNP, but these responses were not different between LH and high hormone phases. In conclusion, our results demonstrate that OCs do not alter cardiovascular and sympathetic neural responses to an orthostatic challenge in young, healthy women.